Computer Adaptive Test Development To Assess Students’ Psychology - Phan Thi Thu Nguyet; Muslem Daud (UNIVERSITAS SERAMBI MEKKAH, 2021)
Stress becomes a significantly serious issue among university students and we need efficient tools to understand it more. The aim of present study is to develop a Computerized Adaptive Testing (CAT) to measure the mentioned stress, as pioneer project in Vietnam. In this vein, an item bank of 68 items has been constructed, which is based on Likert Polytomous Scales through five subdomains: behavior, academic performance, family, lecturer and finance. The sampling of the survey is large. It has assessed 2,085 students (704 males and 1,381 females). Multidimensional Random Coefficients Multinomial Logit (MRCML) Model is applied to develop Multidimensional Stress Scales and Computerized Adaptive Testing procedure. The result findings indicate that Multidimensional Random Coefficients Multinomial Logit (MRCML) can be used to develop new scale with psychometric properties. Indicated by various fit criteria MNSQ, standard errors, Z (t-test) implemented in software ConQuest. The subdomain has a good reliability (from .857 to .798). As respect to CATs, a simulated experiment based on the empirical data is applied to evaluate the performance of the proposed computerized adaptive testing. The standard error of the estimated stress proficiencies are reported in this study. The 68 items stress data appropriate fit the Multidimensional model applied.